2009
DOI: 10.2106/jbjs.g.01485
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Outcomes of Anterior Lumbar Interbody Arthrodesis with Use of Interbody Fusion Cages and Recombinant Human Bone Morphogenetic Protein-2

Abstract: The use of dual tapered threaded fusion cages and recombinant human bone morphogenetic protein-2 on an absorbable collagen sponge obtained and maintained intervertebral spinal fusion, improved clinical outcomes, and reduced pain after anterior lumbar interbody arthrodesis in patients with degenerative lumbar disc disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 20 publications
3
89
1
12
Order By: Relevance
“…7 No significant difference in outcome at 6 years was observed when compared with the previously published data obtained at 2 years after surgery. Geibel et al reported a 100% fusion rate with an 89% patient satisfaction rate in 48 patients undergoing 1-and 2-level instrumented PLIF with rhBMP-2 and posterolateral fusion.…”
Section: Bone Morphogenetic Proteinsmentioning
confidence: 54%
See 1 more Smart Citation
“…7 No significant difference in outcome at 6 years was observed when compared with the previously published data obtained at 2 years after surgery. Geibel et al reported a 100% fusion rate with an 89% patient satisfaction rate in 48 patients undergoing 1-and 2-level instrumented PLIF with rhBMP-2 and posterolateral fusion.…”
Section: Bone Morphogenetic Proteinsmentioning
confidence: 54%
“…However, no material has received more attention and generated more controversy than the family of BMPs. There are numerous papers that demonstrate the fusion potential of BMPs; 2,7,18,19 however, complications associated with their use have been reported. 29,47,50 Whether the benefits of BMPs justify the costs remains to be determined.…”
Section: Rationalementioning
confidence: 99%
“…Data from a non-comparative 6 year follow-up study of 128 patients treated with dibotermin alfa/ACIM indicated that the rate of failure-related second surgery reduced from 6.7% during the first 24 months to 3.7% during the period 2-6 years; and the percentage of patients working at 6 months (63%) was higher than pre-operation (52%), which was sustained at 6 years (68%) 35 . Nevertheless, further research is required to study the long-term costs and health benefits of dibotermin alfa/ACIM.…”
Section: Discussionmentioning
confidence: 99%
“…However, BMP has the benefits of decreased operative time, blood loss, donor site morbidity, transmission of infection associated with use of allograft, and rate of pseudarthrosis. 3,9 In a retrospective analysis of 47 patients conducted at our institution, the use of BMP in pediatric patients undergoing occipitocervical, cervical, and thoracic, lumbar, or lumbosacral spine fusion led to no cases of new cancers, tumor degeneration, or metastasis at the 24-month follow-up. 37 To the best of our knowledge, no other studies have been published reporting the use of transsacral pedicle screws in adolescents with high-grade spondylolisthesis.…”
Section: Surgical Techniquesmentioning
confidence: 99%